Isotherm and pH Effect Studies of Tetracycline Drug Removal from Aqueous Solution Using Cobalt Oxide Surface - Hami, Hawraa Kassem; Abbas, Ruba Fahmi; Waheb, Ali Amer; Abdul abass, Dhifaf A; Abed, Marwa A; Maryoosh, Asmaa A (Al-Nahrain Journal of Science, 2019)
Tetracycline adsorption on the surface of cobalt oxide studied in this work to determine the appropriate conditions for increasing the efficiency of adsorption by changing the temperature, adsorbed dosages, concentration, contact time and pH. The results showed that the rate of adsorption decreased by increasing the temperature and concentration and at 45 minutes with 0.1 gm of Co3O4. The influence of pH on adsorption at pH (1.2, 6, 8) was studied and concentration with a linear range of (20-70 mg/l), the adsorption ratio decreased by increasing the concentration at the same pH. The point of zero charges pHzc calculated and found to be equal to 7.2. Both Langmuir and Freundlich isotherm studied. The result showed a good agreement with Freundlich linear model.